The role of attachment style in interpersonal psychotherapy for depressed adolescents. (2nd January 2019) - Gunlicks-Stoessel, Meredith; Westervelt, Ana; Reigstad, Kristina; Mufson, Laura; Lee, Susanne
Abstract: Objective(s): This study examined changes in depressed adolescents' reports of attachment anxiety and avoidance with interpersonal psychotherapy (IPT-A), and the relationship between attachment style and change in depression with IPT-A.Method: Forty adolescents (aged 12–17) participated in a 16-week randomized clinical trial of 4 adaptive treatment strategies for adolescent depression that began with IPT-A and augmented treatment for insufficient responders ( n = 22) by adding additional IPT-A sessions ( n = 11) or the antidepressant medication, fluoxetine ( n = 11). Adolescents were 77.5% female and 22.5% male (mean age = 14.8, SD = 1.8). Ten percent of adolescents were Latino. Racial composition was 7.5% Asian, 7.5% American Indian/Alaska Native, 80.0% white, and 5.0% biracial. Measures of attachment style (Experience in Close Relationships Scale—Revised [ECR-R]) and depression (Children's Depression Rating Scale—Revised [CDRS-R]) were administered at baseline and Weeks 8 and 16.Results: Attachment Anxiety and Avoidance (ECR-R) decreased significantly from baseline to Week 16. Baseline Avoidance positively predicted greater reductions in depression (CDRS-R), controlling for fluoxetine. Reductions in Anxiety and Avoidance were also significantly associated with reductions in CDRS-R, controlling for fluoxetine.Conclusions: Adolescents' reports of attachment anxiety and avoidance are amenable to intervention with IPT-A. IPT-A may be particularly beneficial for adolescents who report a high level of avoidant attachment. Clinical or methodological significance of this article Our findings suggest that attachment anxiety and avoidance are constructs that are amenable to intervention during adolescence, and therefore viable targets of treatment. IPT-A was found to be an effective intervention for addressing problems in attachment style, and decreases in attachment anxiety and avoidance were associated with reductions in depression. This provides support for selecting IPT-A as a treatment option for adolescents who are depressed and describe difficulty with attachment security. IPT-A appears to be particularly effective for adolescents with an avoidant attachment style, who experience discomfort with and have a tendency to avoid intimacy.